Dinâmicas territoriais na Amazônia paraense: da relação entre planejamento regional e espaço agrário à pecuária bovina em Novo Repartimento-PA - RIBEIRO, Mílvio da Silva (Universidade Federal do Pará, 2023)
The present research defends the thesis that the agrarian dynamic of the Paraense Amazon results from the relationship between agrarian space and state planning. This relationship was verified in the dynamics of cattle ranching in Novo Repartimento-PA. The objective of the research was to analyze the relationship between regional planning and agrarian space, in the municipality of Novo Repartimento, considering the dynamics of cattle ranching on pasture. Methodologically, the research is structured in two moments: in the first moment, a contextual retrospective was elaborated that shows policies, plans and programs forged for the Paraense Amazon, specifically from the 1960s until 1980. In the second moment, the research was configured in a perspective in which cattle ranching is considered as determined from the relationship between agrarian space and regional planning, examined in the period from 1990 to 2020. The central variables of the research related to the dynamics of cattle ranching were areas (deforestation in rural properties) and landscape unit (pastures). The research points out that the relationship between regional planning and agrarian space in the Eastern Amazon, objectively in the municipality promotes spatial processes, having as its logic, cattle ranching as a commodity and social relation. The forms of land appropriation are not only elements of the production of cattle ranching, but they generate other forms of uses. The expansion of the activity in the municipality disqualifies the characteristics and cultural actions of the players, who resided before the arrival of cattle ranching in the area. The state, programs, projects and laws are configured in the agrarian space in the form of credits and tax incentives, which favor the expansion of cattle ranching. In this way, the spatial dynamics of cattle ranching occurs as a forest-policy-pasture-grown-market-consumption continuum. The ranches and the oxen are the physical expressions of the relationship between space and politics, but it is only the tip of the iceberg, because there are other problems arising from the context of commodity production in the Amazon. The research is organized as follows: Introduction and four chapters (the first, deals with Planning and Agrarian Space, as conceptual terms and the contextual situations of the research; the second, presents Regional Planning and ranching in the middle Tocantins River between 1960 and 1980; the third, addresses the Conversion of forests into pastures in Novo Repartimento-PA; and in the fourth, State Planning and ranching in Novo Repartimento-PA were discussed); finally, the final considerations of the research are presented.